2018
DOI: 10.1111/anu.12670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary zinc level on performance, zinc status, tissue composition and enzyme activities of juvenile Siberian sturgeon, Acipenser baerii (Brandt 1869)

Abstract: This study conducted to evaluate the effect of dietary zinc (Zn) levels on feed utilization, tissue Zn composition and serum enzyme activities of juvenile Siberian sturgeon, Acipenser baerii. Five isoenergetic and isonitrogenous semi‐purified diets were formulated with increasing Zn sulphate (ZnSO4.5H2O) level to provide the actual Zn values of 14.7 (control), 20.8, 27.3, 37.7 and 46.4 mg/kg diet. Each diet was assigned to three groups of 20 experimental Siberian sturgeons with uniform size (initial weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…Thus, AKP can be used as an important indicator to evaluate Zn status in aquatic animals (27) . In the present study, AKP activity in haemolymph was higher in crabs fed the diets containing 68•5 and 97•3 mg/kg Zn compared with crabs fed the other diets, and similar results were found in blunt snout bream (Megalobrama amblycephala) (27) , grass carp (44) , Indian major carp (20) , Nile tilapia (60) and Siberian sturgeon (Acipenser baerii) (61) .…”
Section: Discussionsupporting
confidence: 85%
“…Thus, AKP can be used as an important indicator to evaluate Zn status in aquatic animals (27) . In the present study, AKP activity in haemolymph was higher in crabs fed the diets containing 68•5 and 97•3 mg/kg Zn compared with crabs fed the other diets, and similar results were found in blunt snout bream (Megalobrama amblycephala) (27) , grass carp (44) , Indian major carp (20) , Nile tilapia (60) and Siberian sturgeon (Acipenser baerii) (61) .…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, activities of these antioxidant enzymes could serve as a biomarker of the antioxidant defense status of the organism. SOD is one of the antioxidant proteins that catalyze the rapid dismutation of superoxide radicals (O 2− ) into molecular oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ), while GPX and CAT promote the conversion of H 2 O 2 to water and oxygen, thereby providing cellular defense against oxidative damages (51)(52)(53). In the present study, SOD and CAT activities increased with increasing dietary FA-coated nanochitosan supplementation up to 0.50 mg kg −1 and thereafter tended to decline, which is in accordance with studies on murrel, Channa punctata (10), grouper (14), and Siberian sturgeon (16).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Zn concentration in the liver of tilapia increased as Zn supplementation in the diet exceeded the optimal requirement level (Huang et al, 2015). Similarly, the Zn content in the liver of juvenile Siberian sturgeon ( Acipenser baerii ) was enhanced by feeding the animal with a diet containing 37.7 mg/kg Zn (Moazenzadeh et al, 2018). In addition to the effect of dietary Zn on the Zn content in the tissue, Zn also participates in the metabolism of proteins, carbohydrates and other nutrients in animals (Vallee & Falchuk, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In intensive aquaculture, the precise need for dietary nutrition in economically important species needs to be determined to improve animal growth and health. The necessity of adding mineral nutrients in feed has recently attracted wide attention (Fisheries Bureau of Agriculture Ministry of China, 2020) because micronutrient intake is closely related to the health and immunity of aquatic animals (Moazenzadeh et al, 2018; Yuan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation